Endoscopic Ultrasound-Guided Liver Biopsy Using a Core Needle for Hepatic Solid Mass - Hyung Ku Chon; Hee Chan Yang; Keum Ha Choi; Tae Hyeon Kim (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims This study aimed to evaluate the feasibility and efficacy of endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) using a core needle for hepatic solid masses (HSMs). Additionally, the study aimed to assess factors that influence the diagnostic accuracy of EUS-FNB for HSMs. Methods A retrospective analysis of patients who underwent EUS-FNB for the pathological diagnosis of HSMs was conducted between January 2013 and July 2017. The procedure had been performed using core needles of different calibers. The assessed variables were mass size, puncture route, needle type, and the number of needle passes. Results Fifty-eight patients underwent EUS-FNB for the pathologic evaluation of HSMs with a mean mass size of 21.4±9.2 mm. EUS-FNB was performed with either a 20-G (n=14), 22-G (n=29) or a 25-G core needle (n=15). The diagnostic accuracy for this procedure was 89.7%, but both specimen adequacy for histology and available immunohistochemistry stain were 91.4%. The sensitivity and specificity of EUS-FNB were 89.7% and 100%, respectively. There was one case involving bleeding as a complication, which was controlled with endoscopic hemostasis. According to the multivariate analysis, no variable was independently associated with a correct final diagnosis. Conclusions EUS-FNB with core biopsy needle is a safe and highly accurate diagnostic option for assessing HSMs. There were no variable factors associated with diagnostic accuracy.